Предмет: Математика,
автор: Alya19982002
приведите уравнениe(х-5)(2х+3)- (х+4)(4-х) = 2х + 5 к виду ах^2 + bx + c =0
Ответы
Автор ответа:
0
(2x^2+3x-10x-15) - (x^2-16)=2x+5
2x²-7x-15 - x²+16 -2x-5=0
x² - 9x - 4 = 0
Перепроверь
2x²-7x-15 - x²+16 -2x-5=0
x² - 9x - 4 = 0
Перепроверь
Автор ответа:
0
спасибо
Автор ответа:
0
Пожалуйста
Похожие вопросы
Предмет: География,
автор: zarinarisuper
Предмет: Математика,
автор: LUBA195919591959
Предмет: Русский язык,
автор: kolyass009
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: SoNyA1607